2019
DOI: 10.1101/2019.12.12.873901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tubular STAT3 limits renal inflammation in autosomal dominant polycystic kidney disease

Abstract: words)The inactivation of the ciliary proteins polycystin 1 or 2 leads to autosomal dominant polycystic kidney disease (ADPKD), the leading genetic cause of chronic kidney disease. Both cilia signaling and interstitial inflammation play a critical role in the disease. Yet, the reciprocal interactions between immune and tubular cells are not well characterized. The transcription factor STAT3, which is suspected to fuel ADPKD progression, is involved in crosstalks between immune and non-immune cells in various t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Larger numbers and additional studies on the interplay between cyst-lining epithelial signalling and, for example, interstitial inflammatory processes, functional mapping in full-length fibrocystin, and studies on the effects of the observed SRC-induced FC phosphorylation on the non-conserved tyrosine 3992 are required. 15 In summary, we show increased activation of SRC and STAT3 in cyst-lining epithelia of ARPKD kidneys. Mechanistically, our data suggest that the carboxy-terminus of human FC can contribute to control of SRC-activation.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Larger numbers and additional studies on the interplay between cyst-lining epithelial signalling and, for example, interstitial inflammatory processes, functional mapping in full-length fibrocystin, and studies on the effects of the observed SRC-induced FC phosphorylation on the non-conserved tyrosine 3992 are required. 15 In summary, we show increased activation of SRC and STAT3 in cyst-lining epithelia of ARPKD kidneys. Mechanistically, our data suggest that the carboxy-terminus of human FC can contribute to control of SRC-activation.…”
Section: Discussionmentioning
confidence: 52%
“…This activation showed some variability amongst patients with different clinical courses. Larger numbers and additional studies on the interplay between cyst‐lining epithelial signalling and, for example, interstitial inflammatory processes, functional mapping in full‐length fibrocystin, and studies on the effects of the observed SRC‐induced FC phosphorylation on the non‐conserved tyrosine 3992 are required 15 …”
Section: Discussionmentioning
confidence: 99%
“…However, while STAT3 activation was increased in Pkd2;Thm1 dko mice, fibrosis as assessed by αSMA staining was not. In contrast to studies suggesting a pathogenic role for increased STAT3 signaling, a recent study has shown that tubular STAT3 activation restricts immune cell infiltration in Pkd1 cko mice 32 . Genetic deletion of Stat3 together with Pkd1 in renal tubular cells slightly reduced cystic burden, but did not ameliorate kidney function and increased interstitial inflammation.…”
Section: Discussionmentioning
confidence: 73%
“…A well-characterized role for primary cilia is Hedgehog (Hh) signal transduction, which generally requires primary cilia to potentiate downstream intracellular signaling (17,19). It has been established that the transcription factor signal transducer and activator of transcription 3 (STAT3), which can be activated by various proinflammatory cytokines, promotes ciliogenesis (20)(21)(22). Uterine Stat3 deficiency causes decidualization failure in mice (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Both intraflagellar transport protein IFT88 and Joubert syndrome protein ARL13B are required for cilia assembly and Hh signal transduction ( 25 , 26 ), whereas the histone deacetylase HDAC6 and the kinase Aurora A are important for cilia disassembly ( 27 ). The dysfunction of primary cilia results in multisystemic genetic ciliopathies such as polycystic kidney disease ( 21 ). Although recent single-cell transcriptomic analyses indicate that motile cilia are present in endometrial epithelial cells throughout the human menstrual cycle ( 28 , 29 ), whether primary cilia are present in the mammalian uterus remains unsolved.…”
Section: Introductionmentioning
confidence: 99%